Intrauterine valproate exposure is associated with alterations in hippocampal cell numbers and folate metabolism in a rat model of valproate teratogenicity. (March 2017) - Semmler, Alexander; Frisch, Christian; Bleul, Christiane; Smith, Desiree; Bigler, Laurent; Prost, Jean-Christophe; Blom, Henk; Linnebank, Michael
Highlights: Intrauterine VPA exposure leads to changes in hippocampal cell numbers and in folic acid metabolism. Surprisingly, acetylation of histones and global DNA methylation are unaltered in brain tissue. Further investigation of VPA teratogenicity and of of folate supplementation remains necessary. Abstract: Purpose: Valproate is one of the most commonly used anticonvulsive drugs. Despite its significant benefits, the teratogenicity of valproate is a relevant problem in the treatment of women of childbearing age. In addition to major congenital malformations, such as neural tube defects, reduced intelligence and attention after intrauterine valproate exposure are reported. Until now the mechanisms of teratogenicity of VPA are poorly understood and concepts how to reduce valproate teratogenicity are lacking. Methods: In a rat model of valproate teratogenicity we examined hippocampal cell structure in 4 week old animals with a stereological approach. As potential mechanisms of VPA teratogenicity we examined histone acetylation by western blotting and metabolites of the folate metabolism as well as global DNA methylation by tandem mass spectrometry in the brain and liver tissue of newborn pups (p0). Results: We found an increase in the number of neurons in the hippocampal areas CA1/2 (p = 0.018) and CA3 (p = 0.022), as well as a decreased number of astrocytes in CA1/2 (p = 0.004) and CA3 (p = 0.003) after intrauterine VPA exposure, as a possible indication of altered cell differentiation during intrauterine VPA exposure. Valproate exposure was also associated with an increase in 5-methyl-tetrahydrofolate (THF) (p = 0.002) and a decrease in 5-10-methenyl-THF in the brain of newborn pups, as well as a reduced homocysteine plasma level (p < 0.001). The described changes in hippocampal cell numbers and folate metabolism were only significant after high-dose intrauterine VPA exposure indicating a dose-dependent effect. VPA exposure was not associated with changes in histone acetylation or global DNA methylation in brain tissue in newborn pups. Conclusion: This study shows that intrauterine VPA exposure is associated with changes in hippocampal cell numbers in the CA1/2 and CA3 region and in folate metabolism.